BRAQUIÓPODOS SILÚRICOS DE LAS FORMACIONES TAMBOLAR y RINCONADA EN LA PRECORDILLERA DE SAN JUAN, ARGENTINA (Ameghiniana, 2014)
Articulate brachiopods from Wenlockian strata of the Tambolar Formation (Pachaco locality) and Rinconada Formation (type locality) include Orthostrophella n. sp., Leangella (Leangella) sp., Leptaena sp., Australina sp., Howellella? sp. and Harringtonina? sp. In addition, /sorthis (Protocorterorthis) sp. and Nuc/eospira sp. were recovered from Late Ludlowian-Pridolian beds near the top of the Tambolar Formation at the type locality. The new subgenus Dedzetina (Noiodedzetinov is proposed on the basis of well-preserved specimens of Dedzetinat silurica Benedetto from the Lower Member of the Los Espejos Formation at quebrada Salto Macho, south of Talacasto. Spiriferacean brachiopods are recorded for the first time in the Silurian Afro-South American (= Malvinokaffric) Realm. The presence of Howellella? and Nuc/eospira corroborates the high in flux of North Silurian Realm brachiopods in the Precordillera basin during the Mid-Late Silurian.